(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Handloom industries in Trivandrum district play an important role for the economic impact of Trivandrum district. Handloom products in Balaramapuram region have a unique in the world. The number of handloom workers in the middle of 2009-2010 and 2019-2020 has grow by 11.5% with the comparatively expanded in total handloom production. This industry increase our GDP and also our foreign exchange earnings. about 16% of fabric production in India is from the handloom industry. This paper concentrates about the economic impact of handloom industries in Balaramapuram Town.